Revistas especializadas en Biblioteconomía y Documentación en el siglo XIX: El “Boletín Bibliográfico Español y Estrangero” (1842-1868) - López García, Ana Belén (Documentación de las Ciencias de la Información, 2007)
Within the field of specialized (specialised) periodicals, this survey provides data to evaluate and assess one of the most influential periodicals in its field in the 19th century. Readers will be able to know a selection of the most relevant subjects, as well as the more important writers at the time.